Calcium Carbide Residue as a Supplementary Precursor is Geopolymer Binders - Mohammed, Taofiq O.; Singh, Divisha; Fanijo, Ebenezer O. (Frontiers in Materials, 2025)
With the declining availability of conventional supplementary cementitious materials such as fly ash and slag, there is an urgent need to identify alternative aluminosilicate sources for geopolymer synthesis. Calcium carbide residue (CCR), a high-calcium industrial by-product from acetylene production, has shown potential as a sustainable precursor, yet its role in slag-based geopolymer systems remains insufficiently explored. The aim of this work is to evaluate the chemical reactivity, mechanical performance, and microstructural characteristics of slag-based geopolymers incorporating CCR, with and without metakaolin (MK). Mechanical properties were assessed through setting-time measurements and compressive strength testing, while microstructural evolution was examined using standard microstructural and thermal characterization techniques such as XRD, FTIR, TGA and SEM. The incorporation of CCR in the geopolymer mixes influenced setting behavior and strength development over time, with lower CCR content delaying setting by about 13%, while higher dosage or ternary blends with MK accelerated setting behaviour by up to 10% due to synergistic reactivity. Compressive strength results confirmed that the binary mix with lower CCR dosage and the ternary blends containing MK achieved strengths comparable to the control mix, with the ternary blends reaching approximately 96%–99% of the control strength. This highlights their potential as alternative precursors without compromising mechanical performance. Microstructural analyses revealed that CCR alters the gel morphology and phase composition, resulting in a hybrid C–A–S–H and N–A–S–H gel system with a refined pore structure and potentially denser microstructure Furthermore, the ternary combination of slag, CCR, and MK enhances the Si/Al and Ca/Si ratios, facilitating improved polycondensation and the development of a more cohesive and interconnected gel matrix. These findings demonstrate the potential of CCR as a viable precursor in geopolymer systems, contributing to improved structural performance and sustainability by diverting an industrial waste from landfills and reducing reliance on conventional precursors such as slag.